Biodegradable MRI Visible Drug Eluting Stent Reinforced by Metal Organic Frameworks. Issue 14 (16th June 2020) - Hamideh, Rezvani Alanagh; Akbari, Babak; Fathi, Parinaz; Misra, Santosh K.; Sutrisno, Andre; Lam, Fan; Pan, Dipanjan
Abstract: Metal–organic frameworks (MOFs) have applications in numerous fields. However, the development of MOF‐based "theranostic" macroscale devices is not achieved. Here, heparin‐coated biocompatible MOF/poly( ε ‐caprolactone) (PCL) "theranostic" stents are developed, where NH2 ‐Materials of Institute Lavoisier (MIL)‐101(Fe) encapsulates and releases rapamycin (an immunosuppressive drug). These stents also act as a remarkable source of contrast in ex vivo magnetic resonance imaging (MRI) compared to the invisible polymeric stent. The in vitro release patterns of heparin and rapamycin respectively can ensure a type of programmed model to prevent blood coagulation immediately after stent placement in the artery and stenosis over a longer term. Due to the presence of hydrolysable functionalities in MOFs, the stents are shown to be highly biodegradable in degradation tests under various conditions. Furthermore, there is no compromise of mechanical strength or flexibility with MOF compositing. The system described here promises many biomedical applications in macroscale theranostic devices. The use of MOF@PCL can render a medical device MRI‐visible while simultaneously acting as a carrier for therapeutic agents. Abstract : The first metal organic framework (MOF)‐based "theranostic" macroscale stent is developed. Magnetic resonance imaging (MRI) visibility and enhanced biodegradability of the polymeric stent are enabled by MOFs without sacrificing its mechanical properties. Both blood coagulation and restenosis can be responded to through the release of drugs. The as‐prepared MOF‐based stent exhibits significant advantages of MOFs to increase the capabilities of biomaterials.